Comprehensive MEDLINE fulltext - National Library of Medicine (U.S.); EBSCO Publishing (Firm) (Ipswich, MA : EBSCO Pub.)
Commercial CD-ROM version of MEDLINE, developed by the National Libr ary of Medicine. Subjects include all aspects of clinical medicine (dis eases and disorders, diagnostic and therapeutic techniques and equipmen t), basic biomedical sciences (anatomy, physiology, biochemistry, genet ics, microbiology, pharmacology, etc.), the health care system (facilit ies, manpower, services, administration), dentistry, nursing, and clini cal psychology. Also includes information on diagnosis, etiology, thera py, and prevention of diseases and disorders; on research in basic scie nce fields relating to medicine; and on biomedical technology and its a pplications.
Description based on: Dec. 2000; title from disc label.
Issued in multiple discs. Discs for <2000-> cover <Jan. 1990-Dec. 20 00> and include additional retrospective coverage, called: Backfile <T- Z> covering: <Jan. 1966-Feb. 1988>. Also included: Windows installation disc.
Discs 2-10 and Backfile S-Z, for 2000, revised May 2000.
System requirements: IBM PC or compatible; Windows; CD-ROM Drive.
Keywords: Medicine -- Periodicals -- Indexes -- Periodicals; Medicine -- Periodicals -- Abstracts -- Periodicals